2019
DOI: 10.1021/acs.jpcb.9b04058
|View full text |Cite
|
Sign up to set email alerts
|

Gas or Liquid? The Supercritical Behavior of Pure Fluids

Abstract: By definition, the distinction between a gas and a liquid ceases to exist beyond the critical point for pure fluids. Nevertheless, there remains a strong desire to attribute gas-like or liquid-like behavior to fluids corresponding to different parts of the supercritical region, especially as this becomes important for understanding and designing the properties of supercritical fluids. Here, we use a combination of fluctuation solution theory and accurate equation of state data to elucidate an easily accessible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 98 publications
1
15
0
Order By: Relevance
“…However, over the last two decades, it was found that SCFs may exhibit more liquid-like (LL) or gas-like properties as pressure, temperature, or density are varied across appropriate regions in state space 10 18 . It must be emphasized that these qualifications always refer to specific characteristics such as sound dispersion 10 , 11 , unexpected variations in thermodynamic response functions 12 , or correlations in density fluctuations 19 , and always imply continuous variations of all relevant observables 20 .…”
Section: Introductionmentioning
confidence: 99%
“…However, over the last two decades, it was found that SCFs may exhibit more liquid-like (LL) or gas-like properties as pressure, temperature, or density are varied across appropriate regions in state space 10 18 . It must be emphasized that these qualifications always refer to specific characteristics such as sound dispersion 10 , 11 , unexpected variations in thermodynamic response functions 12 , or correlations in density fluctuations 19 , and always imply continuous variations of all relevant observables 20 .…”
Section: Introductionmentioning
confidence: 99%
“…This fascinating possibility of a continuous transformation from gaseous to liquid states of matter has attracted attention since the seminal experiments of Andrews back in 1869 . More recently, the possibility of defining a demarcation between liquid- and gas-like behaviors for the whole supercritical domain has been the subject of numerous investigations. ,, Determining such a signature of a subcritical behavior, where the gas and liquid phases are distinct, in the supercritical region is of obvious fundamental interest but would also certainly be beneficial for the design of modern equation of states and transport properties models. This topic has led to many debates, which were particularly vivid during the past decade, because of multiple definitions often not compatible which one another, even within the same family, for example, Widom Lines, inversion lines, or Frenkel lines .…”
mentioning
confidence: 99%
“…1−3 Another transition emanating from the critical point has been proposed very recently. 4 These transitions are essentially thermodynamic continuations of the vapor pressure curve.…”
mentioning
confidence: 99%
“…However, in recent years two separate ideas have been proposed that both contradict this viewpoint. On the one hand, rapid fluctuations in certain thermodynamic properties roughly following the critical isochore close to the critical point, the Widom lines, have been proposed to extend much further beyond T C than previously believed on the basis of the fundamental equation of state (EOS) and to mark a transition to a liquid-like state. Another transition emanating from the critical point has been proposed very recently . These transitions are essentially thermodynamic continuations of the vapor pressure curve.…”
mentioning
confidence: 99%